Pelatihan Berbasis Kompetensi Menggunakan VMWARE Workstation Dan Windows Server 2019 - Derman Janner Lubis; Julio Warmansyah; Arif Harbani; Hidola Syamsito; Ervan Britantono (LP3M Universitas Binaniaga Indonesia, 2025)
This socialization and training activity aims to improve participants' understanding of the importance of creating virtual servers. Creating virtual servers will make it easier to organize resources, manage servers, and coordinate the performance of the server. Vmware workstation functions as a virtual server creation application installed on one physical computer host, while Windows Server 2019 is an operating system installed on Vmware Workstation that functions to manage users, passwords, server file access rights, etc. The implementation of Windows Server 2019 in Vmware Workstation is very necessary so that all students and teachers can use their respective usernames and passwords to access computers at school or in the school computer lab. Thus, using Windows Server 2019 in Vmware Workstation will increase the productivity of students and teachers in using school computers, securing file access rights, and user management in using computers at school.